HOW EARNING PER SHARE (EPS) AFFECTS ON SHARE PRICE - Mira mira ismail (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2021)
This research is a quantitative research using a causality approach that will see and identify the causes and effects of the EPS variable on stock prices. The population in this study are all companies included in the 2018-2019 LQ-45 list, which are 45 companies. The sample was taken based on purposive sampling criteria so that 27 companies were obtained, with the data used were secondary data in the form of published financial statements and can be accessed through www.idx.co.id. The data analysis technique used simple linear regression with SPSS for windows 24.0 test tool. The results of the study show that the EPS variable has a positive and significant effect on the company's share price, this means that EPS is essentially considered important to determine the amount of the stock price and company value, so that most investors can make decisions based on EPS. The evidence that EPS has an effect on stock prices is the 27 companies listed in LQ-45 showing a change in the increase or decrease in the value of EPS which has an effect on the occurrence of an increase or decrease in the Company's stock price.